2016
DOI: 10.1111/acer.13104
|View full text |Cite|
|
Sign up to set email alerts
|

Meta-Analysis Reveals Significant Association of the 3′-UTR VNTR inSLC6A3with Alcohol Dependence

Abstract: Background Although many studies have analyzed the association of 3′-untranslated region (UTR) variable number tandem repeat (VNTR) polymorphism in SLC6A3 with alcohol dependence (AD), the results remain controversial. This study aimed to determine whether this variant indeed has any genetic effect on AD by integrating 17 reported studies with 5,929 participants included. Methods The A9-dominant genetic model that considers A9-repeat and non-A9 repeat as two genotypes and compared their frequencies in alcoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Therefore, despite the fact that SLC6A3 promoter variants are excellent candidates for linkage and association studies, we did not find evidence supporting their role in AD in our cohort of Han Chinese population. For the most investigated 3' UTR VNTRs in relation to AD, two meta-analyses showed inconsistent results [ 16 , 17 ]. The contradictory findings might be attributable to differences in study design such as data sampling and statistical methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, despite the fact that SLC6A3 promoter variants are excellent candidates for linkage and association studies, we did not find evidence supporting their role in AD in our cohort of Han Chinese population. For the most investigated 3' UTR VNTRs in relation to AD, two meta-analyses showed inconsistent results [ 16 , 17 ]. The contradictory findings might be attributable to differences in study design such as data sampling and statistical methods.…”
Section: Discussionmentioning
confidence: 99%
“…The contradictory findings might be attributable to differences in study design such as data sampling and statistical methods. In the latter study, for example, Ma et al [ 17 ] concluded that the 9-repeat allele increased the risk for AD in different populations using a dominant genetic model with a larger sample size. However, the authors did not include two studies that considered that the 9-repeat allele was protective for AD in Japanese and Han Chinese populations [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We searched PubMed and Web of Science for all studies eligible for this meta-analysis according to the PRISMA guidelines 59 , a strategy similar to what we used previously 60 , 61 . The key words used in the search were “ CHRNB3 ” or “ CHRNA6 ” or “cholinergic nicotinic receptor gene” combined with “nicotine dependence” or “ND.” The reports containing the chosen words were checked individually for references that could have been missed by the above-mentioned search protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Since striatal dopamine signaling is directly influenced by dopamine transporter (DAT) availability (Shen et al, 2004, e.g., Giros et al, 1996, Heinz et al, 1999), it has been hypothesized that genetic variation in the gene encoding the DAT ( DAT1/SLC6A3 ) contributes to differences in reward processing (Lohoff et al, 2010, Dreher et al, 2009, Hahn et al, 2011). While several studies have indeed found associations of SLC6A3 variation with various alcohol use disorder phenotypes and endophenotypes (Ma et al, 2016, Ray et al, 2014, Wernicke et al, 2002, Le Strat et al, 2008, Gorwood et al, 2003), other studies were unable to replicate results (e.g., Du et al, 2011, Kohnke et al, 2005, Xu and Lin, 2011). Genetic variation is one important factor influencing interindividual differences in reward processing; however, it is likely that other mechanisms affecting DAT expression or function may also contribute.…”
Section: Introductionmentioning
confidence: 98%